3D printing of electrically conductive and degradable hydrogel for epidermal strain sensor. (January 2023) - Guo, Binbin; Zhong, Yukun; Chen, Xiaoteng; Yu, Shixiang; Bai, Jiaming
Abstract: Owing to superior electrical conductivity, stretchability, and biocompatibility, electrically conductive hydrogels have been widely applied in flexible wearable strain sensors. Generally, conductive fillers are required to be modified to enhance the dispersion stability in hydrogels, increasing the complexity of the experiment. Additionally, due to the intrinsic chemical and physical crosslinking networks, traditional hydrogels are not degradable, resulting in severe environmental pollution problems. Herein, we designed an electrically conductive and degradable hydrogel for the epidermal strain sensor through a facile digital light processing (DLP) three-dimensional (3D) printing technology. A three-step strategy of ultraviolet (UV) curing, ion sputtering, and water spraying was innovatively developed for alleviating the complexity and difficulty in preparing electronic-based hydrogels, and a mono-functional resin curing system was employed to endow hydrogels with promising degradability. This work opens a new path for the preparation of electrically conductive hydrogels and addresses the issues of environmental pollution caused by electronic waste. Graphical abstract: Image 1 Highlights: A strategy of ion sputtering was first introduced in preparing conductive hydrogels. Micro-structured hydrogels were prepared by digital light processing 3D printing. The hydrogel sensor displayed a high gauge factor of 7.2 at 100% strain.